Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: The laplace transform/inverse

  1. Mar 5, 2006 #1
    can someone please help ive been struggling on this problem for 2 days now.

    question is calculate the laplace transform of

    F(P)= 1-P divided by P(squared) + 4P +13

    I realise you have to complete the square as denominator is complex

    When i complete the square i get (P+2) (all squared)+ 3(squared)

    But i cant seem to get the top values of my new partial fraction and im not sure what to do after as ive never come across one of this type before.

    Sorry about the notation but this website wont accept an underline
    Last edited: Mar 5, 2006
  2. jcsd
  3. Mar 5, 2006 #2
    Need a confirmation first. Is your function
    [tex]F(P)=\frac{1-P}{P^2+4P+13}[/tex] or

    (Left-click on one of the equations to see how to write it.)
  4. Mar 5, 2006 #3
    Its the top one.

  5. Mar 5, 2006 #4
    Im also having problem with a laplace differential equation where I get to this point. i dont know how to do a partial fraction with imaginary numbers.

    [tex]Y{(P^2+p-5)}= \frac{1}{P-2} + p+ 3 [/tex]
  6. Mar 5, 2006 #5


    User Avatar
    Homework Helper

    It the same as for real numbers, only that so-called irreduceable quadratics are not so, for example:


    cross-multiply to get


    Now plug-in nice values for P to solve for A and B, best choices for P are [tex]P=-2\pm 3i[/tex] (the zeros of the factors):

    the value [tex]P=-2+3i[/tex] gives

    [tex]3-3i=0+6iB\Rightarrow B=\frac{3-3i}{6i}=-\frac{1}{2}(1+i)[/tex]

    and the value [tex]P=-2-3i[/tex] gives

    [tex]3+3i=-6iA+0\Rightarrow A=\frac{3+3i}{-6i}=\frac{1}{2}(-1+i)[/tex]

    and hence

    [tex]F(P)=\frac{1-P}{P^2+4P+13}=\frac{1-P}{(P+2+3i)(P+2-3i)}=\frac{1}{2}\left[ \frac{-1+i}{P+2+3i}-\frac{1+i}{P+2-3i}\right] [/tex]
    Last edited: Mar 6, 2006
  7. Mar 6, 2006 #6


    User Avatar
    Science Advisor

    If you want to stay in real numbers- don't use partial fractions. Your table of Laplace transforms should have one that gives [itex]\frac{1}{s^2+ a^2}[/itex] and one that gives [itex]\frac{s}{s^2+ a^2}[/itex].
  8. Mar 6, 2006 #7
    I understand now clearly what benorin has done where u put in nice values for p and it follows very clearly but is it does not seem possible to do an inverse transform at that point hence i completed the square but i cant seem to use that method either

    [tex]F(P)=\frac{1-P}{P^2+4P+13}=\frac{?}{((P+2)^2) + (3^2)}=\frac{A}{P+2+3i}+\frac{B}{P+2-3i}[/tex]

    If u dont put it in partial fractions then what do u do?

    BTW i sorted out the other problem

    How do u take inverse transformations with i's in them



    Clearling up these points would i think clear up my problems in laplace.Any ideas
    Last edited: Mar 6, 2006
  9. Mar 6, 2006 #8


    User Avatar
    Homework Helper

  10. Mar 6, 2006 #9


    User Avatar
    Homework Helper

    Check out what HallsofIvy wrote, for that is your solution.
  11. Mar 6, 2006 #10
    i understand that you have to use the tables but i dont understand how u use them with complex components.As i said i know u have to complete the square but i just cant get it and looking at the answer just gets me angry.:mad:

    AS i said ive been trying for ages now
    the other example to clarify things would be helpful as well.Im stuck!!!
  12. Mar 7, 2006 #11


    User Avatar
    Homework Helper

    Inverse Laplace transforms via rean & complex methods

    The real variable method (what HallsofIvy suggested):

    Notation: Suppose that [tex]\ell \{ f(t) \}=F(P)[/tex] is the Laplace transform of f(t), so that [tex]\ell ^{-1} \{ F(P) \}=f(t)[/tex] is the inverse Laplace transform of F(P).

    Work: From



    [tex]\ell ^{-1} \{ F(P)\} =\ell ^{-1} \left\{ \frac{1-P}{P^2+4P+13}\right\} = \ell ^{-1} \left\{ \frac{1-P}{(P+2)^2+9}\right\} = \ell ^{-1} \left\{ \frac{3-(P+2)}{(P+2)^2+3^2}\right\} [/tex]
    [tex]=\ell ^{-1} \left\{ \frac{3}{(P+2)^2+3^2}-\frac{P+2}{(P+2)^2+3^2}\right\} = \ell ^{-1} \left\{ \frac{3}{(P+2)^2+3^2}\right\}-\ell ^{-1} \left\{ \frac{P+2}{(P+2)^2+3^2}\right\} [/tex]
    [tex] = e^{-2t}\ell ^{-1} \left\{ \frac{3}{P^2+3^2}\right\}-e^{-2t}\ell ^{-1} \left\{ \frac{P}{P^2+3^2}\right\}[/tex]

    since [tex] \ell ^{-1} \left\{ F(P-a)\right\} = e^{at}\ell ^{-1} \left\{ F(P)\right\}, [/tex] continuing on we have

    [tex] \ell ^{-1} \{ F(P)\}= e^{-2t}\ell ^{-1} \left\{ \frac{3}{P^2+3^2}\right\}-e^{-2t}\ell ^{-1} \left\{ \frac{P}{P^2+3^2}\right\} = e^{-2t}\sin{3t} - e^{-2t}\cos{3t} ,[/tex]

    where the inverse transforms of sin and cos are off the table.

    In conclusion,

    [tex]\boxed{ \ell ^{-1} \{ F(P)\}= e^{-2t}\left( \sin{3t} - \cos{3t}\right) }[/tex]​

    The complex variable/partial fraction decomposition method (continuing my eariler post): From

    [tex]F(P) = \frac{1-P}{P^2+4P+13} = \frac{1-P}{(P+2+3i)(P+2-3i)} = \frac{1}{2}\left( \frac{-1+i}{P+2+3i}-\frac{1+i}{P+2-3i}\right) [/tex]


    [tex]\ell ^{-1} \{ F(P)\} = \ell ^{-1} \left\{ \frac{1}{2}\left[ \frac{-1+i}{P-(-2-3i)}-\frac{1+i}{P-(-2+3i)}\right] \right\}[/tex]
    [tex] = \frac{1}{2} \ell ^{-1} \left\{ \frac{-1+i}{P-(-2-3i)} \right\} -\frac{1}{2} \ell ^{-1} \left\{ \frac{1+i}{P-(-2+3i)}\right\} [/tex]
    [tex] = \frac{-1+i}{2} \ell ^{-1} \left\{ \frac{1}{P-(-2-3i)} \right\} -\frac{1+i}{2} \ell ^{-1} \left\{ \frac{1}{P-(-2+3i)}\right\}[/tex]
    [tex] = \frac{-1+i}{2} e^{(-2-3i)t} -\frac{1+i}{2} e^{(-2+3i)t} = \frac{-1+i}{2} e^{-2t}e^{-3it} -\frac{1+i}{2} e^{-2t}e^{3it}[/tex]
    [tex] = \frac{e^{-2t}}{2}\left[ (-1+i) e^{-3it} -(1+i)e^{3it}\right] = \frac{1}{2}e^{-2t}\left[ -(e^{3it} +e^{-3it}) -i(e^{3it} -e^{-3it}) \right] [/tex]
    [tex] = e^{-2t}\left[ -\frac{e^{3it} +e^{-3it}}{2} +\frac{e^{3it} -e^{-3it}}{2i} \right] = e^{-2t}\left( -\cos{3t} +\sin{3t}\right) [/tex]

    So, in conclusion, except for the sign error I'm hoping someone will spot for me, we have

    [tex]\boxed{ \ell ^{-1} \{ F(P)\} = e^{-2t}\left( -\cos{3t} +\sin{3t}\right) }[/tex]​
    Last edited: Mar 7, 2006
  13. Mar 7, 2006 #12
    I will spot you,
    It should be -cos and i now see how you bracket things

    Does anybody know about step functions with laplace as again im lost

    let LT of the function g(t) is L(G) = G(p).
    Calculate the Lt of the function

    f(t)= g(t-a) t>a>0
    0, t<a

    Help me get started i cant find any other examples like it.PLEASE
  14. Mar 7, 2006 #13


    User Avatar
    Homework Helper

    PF resources for learning LaTeX Math Typesetting

    This thread will help: PF's Introducing LaTeX Math Typesetting

    An extremely useful excerpt:

    Last edited by a moderator: May 2, 2017
  15. Mar 7, 2006 #14


    User Avatar
    Homework Helper

    Do you mean:

    for [tex]g(t):=\left\{\begin{array}{cc}0,&\mbox{ if }t\leq 0\\1, & \mbox{ if } t>0\end{array}\right.[/tex]

    put [tex]f(t)=g(t-a)=\left\{\begin{array}{cc}0,&\mbox{ if }t\leq a\\1, & \mbox{ if } t>a\end{array}\right.[/tex] ?

    BTW, It looks better like this:

    [tex]\mbox{For } g(t):=\left\{\begin{array}{cc}0,&\mbox{ if }t\leq 0\\1, & \mbox{ if } t>0\end{array}\right. \mbox{, put }f(t):=g(t-a)=\left\{\begin{array}{cc}0,&\mbox{ if }t\leq a\\1, & \mbox{ if } t>a\end{array}\right. ?[/tex]
    Last edited: Mar 7, 2006
  16. Mar 7, 2006 #15


    User Avatar
    Homework Helper

    If so, here it goes...

    For a>0,

    [tex]\mathfrak{L}\{ f(t)\} = \mathfrak{L}\{ g(t-a)\} = e^{-ap}\mathfrak{L}\{ g(t)\} [/tex]

    oops, gives up to much.
  17. Mar 7, 2006 #16


    User Avatar
    Homework Helper

    Thanks, I found it and fixed it.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook